2016
DOI: 10.1097/prs.0000000000002227
|View full text |Cite
|
Sign up to set email alerts
|

Skin-Reduction Breast Reconstructions with Prepectoral Implant

Abstract: Therapeutic, IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 17 publications
4
75
0
1
Order By: Relevance
“…Two articles were excluded; one was a literature review, and the other reported data included in another study. Final screening yielded 14 studies published between 2014 and 2016, including four observational studies comparing pre‐pectoral and dual‐plane reconstruction . Four were congress abstracts, including one in which five authors (A.G., S.S., M.P., L.G., D.M.)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two articles were excluded; one was a literature review, and the other reported data included in another study. Final screening yielded 14 studies published between 2014 and 2016, including four observational studies comparing pre‐pectoral and dual‐plane reconstruction . Four were congress abstracts, including one in which five authors (A.G., S.S., M.P., L.G., D.M.)…”
Section: Resultsmentioning
confidence: 99%
“…Four were congress abstracts, including one in which five authors (A.G., S.S., M.P., L.G., D.M.) were investigators, and the remaining were peer‐reviewed journal articles (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, even though the number of implant-based reconstructions has increased dramatically in the past 10 years (Albornoz et al, 2013), surgeons lack evidence from randomized controlled trials to help women identify the best implant (e.g., silicone vs. saline, variable-volume vs. fixed-volume) (Rocco et al, 2016). Providers need patient-reported outcomes data to help them evaluate new reconstruction methods (e.g., prepectoral implants) (Caputo et al, 2016). Second, women have a short time frame in which to make their decision about whether to undergo immediate versus delayed reconstruction as well as what type of reconstruction to undergo.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several small studies investigated the complication rates in subcutaneous placement. Data are not conclusive as complication rates largely vary (explantation ranges from 0 to 18%, seroma 2-23%, nipple or skin necrosis 1-28%) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. There are three main reasons for this big variance:…”
Section: Introductionmentioning
confidence: 99%